A comparative analysis about bank credit risk determinants in the European Union and the United States - LI, XIN (2019)
The purpose of this paper is to study and compare credit risk determinants of commercial banks in the European 28 countries (EU) and the US by applying a dynamic panel data. This study covers the period from 2011 to 2017 and begins by assuming that both bank-specific and mac-roeconomy variables have impacts on credit risk. Results show that these effects are different between the EU and the US. For the EU, bank inefficiency, GDP growth, capital adequacy, loan loss provision and size are important in explaining credit risk level, while the coefficients of capital adequacy, inflation, loan loss provision are statistically significant in the US.